Challenges of CSR in Sub-Saharan Africa: Clarifying the gaps between the regulations and human rights issues - Achille Gildas Ndong Ntoutoume (International Journal of Corporate Social Responsibility (JCSR), 2023)
This paper discusses the practice of Corporate Social Responsibility (CSR) and its challenges in Sub-Saharan Africa. The main purpose is to highlight and clarify the gaps between CSR regulations and human rights abuses caused by business organizations. From a historical perspective, natural resources have been recognized as a common reason for pushing the CSR agenda in Sub-Saharan Africa, especially with the presence of big businesses in the outcome of globalization. However, despite a development-oriented CSR agenda and therefore on African local needs such as hospitals, housing, and roads, big businesses that have embarked on CSR activities are often involved in human rights violations. This is despite the insertion of human rights in some African state regulations, the UN Global Compact, and the UN Guiding Principles on Business and Human Rights in which those businesses are signatories. This is the case in Gabon, Nigeria, and South Africa whose regulations were established by the respective states indicate business' broader societal priorities directed towards stakeholders (local communities in particular) but in terms of corporate obligations, 'Human Rights appear to be a blind spot in CSR'. The reasons for that are indicated in the findings of this qualitative inquiry, which reveals deep problems of corporate governance and little understanding of corporate human rights in domestic legislation. According to international law, human rights fulfillment focuses on nation-states as sole bearers. This means other non-state actors have indirect human rights responsibilities. Therefore, the challenge remains to extend and interpret existing domestic and international frameworks to include CSR alongside traditional state obligations. This could make corporate human rights more 'applicable' to businesses. Previous research by Visser and Amodu has focused on proposing models to respond to the challenges of CSR in Africa. This paper clarifies the challenges of CSR with human rights issues and suggests an extension of the current legislative framework covering CSR. The article is qualitative and has used a Desk Research study approach that includes published academic papers, government documents some secondary data such as case studies, interviews, and discussions.
Keywords: 650; Business and human rights; CSR; Stakeholders; Sub-Saharan Africa